2022
DOI: 10.3390/molecules27175511
|View full text |Cite
|
Sign up to set email alerts
|

Homologous and Heterologous Expression of Delta(12)-Desaturase in Mucor circinelloides Enhanced the Production of Linolenic Acid

Abstract: Linolenic acid (LA) is gaining more interest within the scientific community. This is because it has a potential medical role in reducing the risk of inflammation, carcinogenesis, atherosclerosis and diabetes and is a valuable nutraceutical for human health. The oleaginous fungus Mucor circinelloides produces a high lipid content (36%), including valuable polyunsaturated fatty acids (PUFAs). However, the critical step in which oleic acid (OA) is converted into LA is not efficient at supplying enough substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…But in previous study, the co-expression of ∆6and ∆12-desaturase was not as effective as the single ∆6-desaturase expression (Zhang et al, 2017). In the present study, the dual overexpression had a higher total fatty acid content (31.7% of CDW) than the single overexpression of DES61 (24.7% of CDW) and DES12 (26.8% of CDW) (Yang et al, 2022), but less than the sum of both. The additional introduction of DES12 in the DES6-overexpressing strain did not increase GLA content (12.8%) compared with the control (13%).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…But in previous study, the co-expression of ∆6and ∆12-desaturase was not as effective as the single ∆6-desaturase expression (Zhang et al, 2017). In the present study, the dual overexpression had a higher total fatty acid content (31.7% of CDW) than the single overexpression of DES61 (24.7% of CDW) and DES12 (26.8% of CDW) (Yang et al, 2022), but less than the sum of both. The additional introduction of DES12 in the DES6-overexpressing strain did not increase GLA content (12.8%) compared with the control (13%).…”
Section: Discussioncontrasting
confidence: 77%
“…In addition, wild-type strain WJ11 was able to accumulate OA (up to 37%), Yang et al enhanced LA content with OA content decreasing by overexpression ∆12-desaturase, which indicated that ∆12-desaturase was the rate-limiting step ( Yang et al, 2022 ). We predicted that co-overexpression of ∆6- and ∆12-desaturase would further elevate GLA production by increasing the production of precursor LA.…”
Section: Discussionmentioning
confidence: 99%